2017
DOI: 10.1038/s41598-017-03795-6
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Antimicrobial Peptide Aurein 1.2 and Charged Lipid Bilayer

Abstract: Aurein 1.2 is a potent antimicrobial peptide secreted by frog Litoria aurea. As a short membrane-active peptide with only 13 amino acids in sequence, it has been found to be residing on the surface of lipid bilayer and permeabilizing bacterial membranes at high concentration. However, the detail at the molecular level is largely unknown. In this study, we investigated the action of Aurein 1.2 in charged lipid bilayers composed of DMPC/DMPG. Oriented Circular Dichroism results showed that the peptide was on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 45 publications
3
40
0
Order By: Relevance
“…Neutron diffraction studies have revealed other mechanisms for the lysis of bilayers by horizontally orientated AMPs involving membrane thinning but not leading to pore or channel formation, such as that recently described for aurein 1.2. The binding of the peptide to membranes induced membrane thinning, accompanied by a major redistribution of PG species in the outer leaflet that appeared to promote the formation of complexes between lipid and aurein 1.2 and the compromise of membrane integrity 58 . A further possibility based on the architecture of M5-MH2 may be that the mode of membrane partitioning used by the peptide leads to the use of a tilted-type mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Neutron diffraction studies have revealed other mechanisms for the lysis of bilayers by horizontally orientated AMPs involving membrane thinning but not leading to pore or channel formation, such as that recently described for aurein 1.2. The binding of the peptide to membranes induced membrane thinning, accompanied by a major redistribution of PG species in the outer leaflet that appeared to promote the formation of complexes between lipid and aurein 1.2 and the compromise of membrane integrity 58 . A further possibility based on the architecture of M5-MH2 may be that the mode of membrane partitioning used by the peptide leads to the use of a tilted-type mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This is interesting as although the potential for the binding of the peptide to induce clustering of POPG was not examined in the present study because of statistical limitations, the finding that Phe 3 was preferentially surrounded by POPG is consistent with results from small-angle neutron scattering experiments that suggested that aurein 1.2 caused the redistribution and clustering of DMPG lipids in a DMPG/DMPC lipid bilayer. 20…”
Section: Discussionmentioning
confidence: 99%
“…So far, there are more than 1200 AMPs that have been identified through the skin secretions of different species (DRAMP database v2.0) [7]. They have generally been classified as Aurein [8], Dermaseptin [9], Phyllseptin [10], Phylloxin [11], generally been classified as Aurein [8], Dermaseptin [9], Phyllseptin [10], Phylloxin [11], and Medusin [12], which are found in Hylidae tree frogs; Brevinin [13], Esculentin [14], Japonicin [15], Nigrocin [16], Palustrin [17], Ranatuerin [18], Ranacyclin [19], and Temporin [20], which are discovered from Ranidae frogs; Kassinatuerin [21], which is isolated from genus Kassina; and Magainin [22], which is discovered from the genus Xenopus.…”
Section: Introductionmentioning
confidence: 99%